ENERGY CONSUMPTION REDUCTION AND EFFICIENCY IMPROVEMENT IN ELECTROCHEMICAL WATER TREATMENT PROCESSES (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2026)
The efficient treatment of industrial wastewater is a critical environmental concern, as many conventional methods are often ineffective for dealing with complex effluents. Electrochemical treatment methods, such as electrooxidation, electrocoagulation, and electroflotation, have been proposed as highly effective alternatives. However, energy consumption remains a key challenge in the widespread adoption of electrochemical processes.